Effects of calcination temperature on structure-activity of K-ZrO2/Cu/Al2O3 catalysts for ethanol and isobutanol synthesis from CO hydrogenation. (1st September 2018) - Li, Xiaoli; Xie, Hongjuan; Gao, Xiaofeng; Wu, Yingquan; Wang, Peng; Tian, Shaopeng; Zhang, Tao; Tan, Yisheng
Graphical abstract: The amount of Cu-ZrO2 interfaces and CuAlO2 phase in K-ZrO2 /Cu/Al2 O3 prepared by impregnation was effectively tuned by calcination temperature. Highlights: K-ZrO2 /Cu/Al2 O3 catalysts were prepared by sequential impregnation method. Calcination temperature tuned the amount of Cu-ZrO2 interfaces and CuAlO2 phase. Isobutanol selectivity was closely related to the Cu-ZrO2 interfaces amounts. The CuAlO2 phases significantly favored ethanol formation. Abstract: A series of K-ZrO2 /Cu/Al2 O3 catalysts (KZC T A ( T = 600–900 °C)) were prepared by a sequential impregnation method and investigated for the direct synthesis of ethanol and isobutanol from syngas. The calcination temperature for C T A ( T = 600–900 °C) preparation had considerable effect on the structure and catalytic performance of KZC T A catalysts. By increasing the calcination temperature from 600 to 900 °C, the CO conversion was promoted obviously from 20.3 to 53.0%. When the calcination temperature was lower, KZC 700 A catalyst showed high isobutanol selectivity of 17.7 wt%, while only a small amount of isobutanol was obtained in the reference catalysts of KZA and KC 700 A without Cu or Zr as promoters. The coexistence of Cu and Zr in the catalyst was required for isobutanol formation. Furthermore, the Cu-ZrO2 interface amounts increased firstly with the increase of calcination temperature and then decreased at over-higher calcination temperature because of the aggregation of ZrO2 . The isobutanol selectivity changed with the Cu-ZrO2 interface amounts in catalyst, suggesting that the Cu-ZrO2 interfaces were responsible for isobutanol preferable synthesis directly from syngas. In addition, ethanol selectivity increased clearly up to 36.3 wt% when the higher calcination temperature 900 °C was employed for catalyst preparation. In comparison with the KZC 900 A catalyst, the catalyst of KC 900 A prepared without Zr as promoter exhibited excellent catalytic performance for the ethanol synthesis (33.5 wt%). It revealed that Zr cannot contribute to ethanol formation, and the newly formed CuAlO2 phase under higher calcination temperature in the catalysts possibly favored ethanol formation. As confirmed by XRD, Raman spectroscopy and H2 -TPR, the CuAlO2 phase emerged and its amount increased with the increase of calcination temperature for catalyst preparation. A good linear relationship was found between ethanol selectivity and the amount of CuAlO2, proving that the CuAlO2 phase acted as efficient active sites for ethanol preferable synthesis directly from syngas.